THE EFFORT TO RESOLVE LAND DISPUTES OVER FORMER LAND OF CULTIVATION RIGHT IN JENGGALU VILLAGE, SELUMA REGENCY, BENGKULU PROVINCE - Rian Putranto; Edra Satmaidi; Herawan Sauni (Bengkoelen Justice : Jurnal Ilmu Hukum, 2023)
The dispute over the former land of cultivation rights (further will be abbreviated and referred as HGU) on behalf of Sahabudin is an area of ​​65 hectares known to have been controlled by the community, and it is known that he has 29 Ownership Certificates (further will be abbreviated and referred d as SHM), and 2 Land Certificates (further will be abbreviated and referred as SKT) belonging to the community, and the ex-HGU land is distributed by agreement. In the regulations, it is clear that the ex-HGU land is returned to the state, and it is clear that the land can no longer be used for other activities. Juridically and conceptually, problems related to the object of land use rights that come from land rights do not seem to experience problems and are legally justified as long as the process of relinquishing land rights is based on applicable regulations. However, if the procedure for relinquishing land rights is not carried out properly according to the law, it will trigger a conflict between the original right holder and the holder candidate of the cultivation right or the holder of the cultivation right . Based on the experience in several areas, including in Bengkulu Province, the cause of conflict between communities and plantation companies that use land rights facilities, is due to the dispute over ownership of land rights, especially related to compensation for land and growing crops on land that has been released in past times. The objectives of this research are: (1). To determine and describe the factors that cause the authorization of former land of HGU in Jenggalu Village, Seluma Regency, Bengkulu. (2). To identify and describe the efforts to resolve disputes over former land of HGU in Jenggalu Village, Seluma Regency, Bengkulu. The method of this research is empirical methods, data analysis was carried out in a qualitative juridical manner. The results of the study explained that: (1). The factors causing the dispute over the authorization of former land of HGU in Jenggalu Village, Seluma Regency, Bengkulu Province are the agreement on the distribution of land with Cultivation Rights, Expiration of Cultivation Rights and the issuance of SHM and SKT on HGU lands. (2). Efforts to resolve land disputes with ex-HGU in Jenggalu Village, Seluma Regency, Bengkulu Province are: efforts to settle out of court through the Regional Leadership Coordination Forum (Further will be referred as Forkopimda) meeting and the Land Office and efforts through civil lawsuits at the Tais District Court. Keywords: Settlement, Dispute, Former land of HGU.